2020
DOI: 10.1073/pnas.2006949117
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin B12 and folic acid alleviate symptoms of nutritional deficiency by antagonizing aryl hydrocarbon receptor

Abstract: Despite broad appreciation of their clinical utility, it has been unclear how vitamin B12 and folic acid (FA) function at the molecular level to directly prevent their hallmark symptoms of deficiency like anemia or birth defects. To this point, B12 and FA have largely been studied as cofactors for enzymes in the one-carbon (1C) cycle in facilitating the de novo generation of nucleotides and methylation of DNA and protein. Here, we report that B12 and FA function as natural antagonists of aryl hydrocarb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 48 publications
(49 reference statements)
0
17
0
Order By: Relevance
“…S6A). Because KA is a ligand for AhR, which regulates immune responses and inflammation ( 5 ), we analyzed AhR activation using a previously defined score ( 9 ) and found that AhR activation correlated most positively with KYAT3 expression in the brain and muscle in older males while closely correlating in colon (fig. S6B).…”
Section: Resultsmentioning
confidence: 99%
“…S6A). Because KA is a ligand for AhR, which regulates immune responses and inflammation ( 5 ), we analyzed AhR activation using a previously defined score ( 9 ) and found that AhR activation correlated most positively with KYAT3 expression in the brain and muscle in older males while closely correlating in colon (fig. S6B).…”
Section: Resultsmentioning
confidence: 99%
“…However, a recent study found that an alternate mechanism may also be involved in the development of NTDs independently of one-carbon metabolism. Kim et al found that folate and B12 are competitive antagonists of the aryl hydrocarbon receptor (AhR), a nuclear receptor that binds hydrocarbon compounds, like the poison dioxin, and induces expression not only of detoxifying enzymes, but also of homeostatic and developmental genes [86]. Loss of AhR antagonism by folate or B12 due to deficiency or activation of AhR by known agonists increases AhR activity and mimics symptoms of B9 and B12 deficiency [86].…”
Section: Developmental and Neurological Consequences Of B9/b12 Deficimentioning
confidence: 99%
“…This blastic change can even lead to the misdiagnosis of leukemia in B12-deficient patients [90,91] and is most often attributed to a maturation arrest of cells due to impaired DNA synthesis from altered one-carbon metabolism [89]. However, activation of the aryl hydrocarbon receptor, potentially from loss of antagonism due to B12 or folate deficiency, can also cause megaloblastic anemia [86], so this alternate mechanism must not be ruled out and can be explored further in clinical studies.…”
Section: Hematological Consequences Of B9/b12 Deficiencymentioning
confidence: 99%
“…4a ). Because KA is a ligand for AhR which regulates immune responses and inflammation 6 , we analyzed AhR activation using a previously defined score 10 and found that AhR activation correlates most positively with KYAT3 expression in older males in brain and muscle, while closely correlating in colon ( Extended Data Fig. 4b ).…”
Section: Kynurenic Acid Is Associated With a Sex-specific Immune Respmentioning
confidence: 99%